Pendidikan Etika: Professi, Politik dan Agama - Mikhael Dua (Respons: Jurnal Etika Sosial, 2008)
Good life is the final purpose of all men. Since Aristotle, ethics is supposed to achieve this purpose. It is a reflection of how to get good life. According to this philosophical assumption, being wealthy and briliant never guarantee the quality of human person. This article talks about a good life in its relation with man as individual, and social being.Kata Kunci: Etika, Kehidupan yang baik, persoalan sosial dewasa ini